العلاقة التكاملية بين المسجد والمدرسة دراسة تحليلية من منظور سوسيولوجيا البنائية الوظيفية لتالكوت بارسونز - غربي, خالد; مسعي احمد, محمد (جامعة الوادي - University of Eloued, 2022)
يعتبر كل من المسجد والمدرسة من أهم المؤسسات الاجتماعية التي تعنى بعملية التربية أو التنشئة الاجتماعية في المجتمع، فالمسجد له مكانة روحية وعقدية، وتأثيرات في جميع مناحي حياة الإنسان المسلم، ويتميز بتلك الحالة القدسية التي تنشر جوا روحانيا في المجتمع، تعمل على تربية الفرد بغض النظر عن المرحلة العمرية التي يمر بها. اما المدرسة تعمل على تهيئة بيئة تربوية بيداغوجية مناسبة من خلال تفاعل المكونات الأساسية في البناء المدرسي والمتمثلة في الجانب المادي، والبشري، والمعنوي. اذ تتفاعل هذه المكونات فيما بينها من أجل تهيئة بيئة تعمل على تربية الافراد بطريقة مقصودة وممنهجة. وعليه فان هذه الورقة تهدف الى معرفة العلاقة التربوية التكاملية بين المؤسسة الدينية (المسجد) والمدرسة وذلك في ضوء ما أثارته النظرية البنائية الوظيفية لبارسونز، ومدى تحقق المتطلبات الوظيفية لأداء الأدوار في المجتمع لكل من المسجد والمدرسة. Abstract: The mosque and the school considered one of the most important social institutions concerned with the process of education or socialization in society. The mosque has a spiritual and nodal status and influences in all aspects of the life of the Muslim human being. It's characterized by that sacred situation, which spreads a spiritual atmosphere in society, and works to raise the individual regardless of the age he is going through. The school works to create an appropriate pedagogical educational environment through the interaction of the basic components of the school's construction, which are physical, human and moral. These ingredients interact in order to create an environment that works to raise individuals in a deliberate and systematic manner. Accordingly, this paper aims to learn about the complementary educational relationship between the religious institution (mosque) and the school in the light of what was raised by Parsons' functional constructive theory and the extent to which the functional requirements for performing roles in society have been met for both the mosque and the school.
The complementary relationship between the mosque and the school Analytical study from the perspective of the functional constructivist sociology of Talcott Parsons
مقال
Keywords: المدرسة، المسجد، المتطلبات الوظيفية، البناء الاجتماعي، التكامل التربوي.; school, mosque, functional requirements, social construction, educational integration.